Inhibition of zymosan-induced kidney dysfunction by tyrphostin AG-490 - Saso Luciano; Shalova Irina; Gyurkovska Valeriya; Dimitrova Petya; Ivanovska Nina (BMC, 2009)
Abstract Background Zymosan-induced shock has been associated with an increased production of pro-inflammatory cytokines and mediators, causing a generalized dysfunction of liver, lung and kidneys. Herein, we investigate the effects of tyrphostin AG-490 on the early inflammation and on the late renal injury provoked by zymosan injection. Methods Shock was induced by intraperitoneal injection of zymosan in a dose of 0.8-1.0 mg/g body weight in BALB/c mice and 0.8 mg/g body weight in SCID mice. Tyrphostin AG-490 was administered intraperitoneally in a dose of 5 mg/kg immediately after shock induction. Blood, peritoneal lavage and kidneys were collected at certain time points after zymosan injection. The levels of MIP-1α, RANTES, IL-6, IL-10, α1-antitrypsin and C5a in plasma were determined by ELISA. The number of IL-10-secreting cells in peritoneum was assayed by ELISPOT. Kidney function was monitored by measurement of urine/plasma creatinine levels and proteinuria. Histological assessment of renal injury was performed in a blinded fashion after hematoxylin/eosin staining. Immunohistochemistry analyses were used to evaluate the expression of C5aR, STAT1, STAT3 and the binding ability of IgGs in kidneys. Results Tyrphostin AG-490 attenuated the early phase of zymosan-induced shock via inhibition of MIP-1α, RANTES and C5a plasma levels and via elevation of IL-10 in plasma. The drug increased IL-10 production in peritoneum and the number of IL-10-secreting peritoneal cells. AG-490 was able to retain the time of coagulation and the level of α1-antitrypsin to normal values. At the late stage of shock, AG-490 decreased scores of tubular injury, cell infiltration and glomerular lesions in parallel with diminished creatinine plasma level and protein excretion. These beneficial effects of AG-490 were related to lowered levels of circulating IL-6, MIP-1α and C5a, and to inhibited expression of STAT1, STAT3 and C5aR in kidneys. The drug diminished the production of zymosan-specific IgG antibodies and hindered the glomeruli from IgGs recognition. Conclusion Tyrphostin AG-490 reduced the magnitude of the initial inflammatory response in zymosan-induced shock and prevented the development of severe kidney dysfunction. Our data suggest that the drug might be used as a therapeutic approach in cases where shock is combined with acute renal injury.